Effects of Lysinibacillus sphaericus on Physicomechanical and Chemical Performance of OPC Blended with Natural Tuff and Pulverized Fly Ash - Kelvin Mwangi Wanjiku; Jackson Wachira Muthengia; Joanne Ogunah; Daniel Karanja Mutitu; John Kinuthia; Romano Mwirichia; Joseph Karanja Thiong’o; Munyao Onesmus Mulwa; Muriithi Genson; Peter Waithaka; David Musyoki Munyao (Advances in Materials Science and Engineering)
This paper reports study findings on the use of Lysinibacillus sphaericus (at 1.0 × 107 cells/ml concentration) to enhance and improve the physicomechanical and chemical properties of blended Ordinary Portland Cement (OPC). Blending was done separately with pulverized fly ash (PFA) and natural pozzolana (volcanic tuff) at substitution levels of 10%, 20%, 30%, 40%, 50%, 60%, and 70%. Mortar prisms of dimensions 40 mm by 40 mm by 160 mm were prepared and cured for the 2nd, 7th, 28th, 56th, and 90th days using Lysinibacillus sphaericus solution as mixing water and curing media. Commercial OPC and PPC mortar prisms cast and cured using distilled water were used as controls. Results showed that prisms treated with bacteria exhibited the highest performance on compressive strength development. Further microstructure analysis of blended cement incorporated with Lysinibacillus sphaericus bacteria showed significant amounts of reacted secondary cementitious materials compared to samples without bacteria. Bacteria presence was also found to reduce water demand during mixing and setting times and exhibited low porosity in relation to samples without bacteria. These results showed that the presence of alkaliphilic bacteria in the blended cement resulted in synergistic effect in enhancing the physicochemical and mechanical properties.